The Motivation of Public Administration Authority Acts - A Dimension of the Right to be Informe - Oana ŞARAMET (JUS ET CIVITAS. A Journal of Social and Legal Studies. Vol. VI (LXX) No. 1 /2019, 2019)
Each of us desires a good administration in which public authorities would exercise their competence only to achieve public interest, without any damage to the rights and liberties of the citizens. In order to have such an administration, it must respect some principles, some rules such as the acts they elaborate, whether they are individual or laws, serve the general interest and not a personal benefit of the people who hold public offices. The main principles are that of transparency of decisions and the motivation of administrative acts; once these principles are respected, the administration will be unable to perform poorly. The current paper aims to analyze some aspects regarding the motivation of administrative acts. Thus, we will attempt to identify the constitutional requirement of motivating the administrative acts, as well as the freedom of speech, the right to be informed, by analyzing Romanian constitutional regulations, as well as some regulations of international structures in Europe. We will also analyze the points of view expressed by doctrine regarding the necessity of such a motivation, as well as the extent of this obligation and its dimension in relation to individual administrative acts or texts of law.
Keywords: right; freedom; express; information; motivation of an administrative act